3D spray-coated gradient profile ceramic membranes enables improved filtration performance in aerobic submerged membrane bioreactor. (15th July 2022) - Gu, Qilin; Ng, Tze Chiang Albert; Poh, Weijie; Kirk, Chin Ho; Lyu, Zhiyang; Zhang, Lei; Wang, John; Ng, How Yong
Highlights: 3D spray-coating technique was adopted to fabricate ceramic membranes (CMs). Fabrication of large-sized gradient profile CMs was demonstrated. Gradient CMs were firstly evaluated in aerobic membrane bioreactors (AeMBR). A slower rise in transmembrane pressure was observed in gradient CMs. Membrane fouling of gradient CMs in AeMBR was clarified. Abstract: Rational design of cross-sectional microstructure in ceramic membranes has shown to improve membrane filtration efficacy without affecting rejection performance. In this work, we adopted 3D spray-coating technique to generate multi-layered membrane layers on macro-porous flat-sheet ceramic supports. The thickness of each layer was controlled by spray-coating cycles, and a gradient membrane layer was rationalized by successively coating three ceramic slurries containing alumina powders of gradually refined particle sizes, followed by co-sintering. Gradient membrane layers on both sides of the various sized flat-sheet ceramic supports were fabricated. Compared to the non-gradient counterpart, the gradient membranes showed both higher pure water flux (at the same TMP) and lower membrane resistance, which clearly evidenced the benefits of gradient profile in the membrane layer. Further, their performance in aerobic membrane bioreactors (AeMBR) was comparably studied for the first time. The treatment performance was not significantly affected by the types of membranes used, while the gradient membrane showed better filtration performance ( i.e., a slower rise in TMP). Although the fouling mechanisms were revealed to be similar, the fouling layer in the gradient membrane was composed of a higher percentage of smaller foulants compared to that of the non-gradient counterpart. The observed differences were closely correlated to the larger internal pore structure in the gradient membrane. The present work provides a feasible 3D spray-coating technique for the fabrication of gradient flat-sheet ceramic membranes, and clarifies the benefits in AeMBR for domestic wastewater treatment. Graphical abstract: Image, graphical abstract